Prostogrit mitigates testosterone/estradiol induced prostatic enlargement/remodeling in rat model of benign prostatic hyperplasia and fine-tunes prostatic expression of Adra1a and Il6 genes - Balkrishna, Acharya; Sinha, Sandeep; Pamidiboina, Venu; Tomer, Meenu; Singh, Rani; Dev, Rishabh; Varshney, Anurag (Frontiers in Endocrinology, 2025)
BackgroundBenign prostate hyperplasia (BPH), the pathological basis of benign prostatic syndrome (BPS), is an ageing-associated, androgen-driven, non-malignant growth of the prostate, with an inflammatory etiology. It is characterized by hyperproliferation of prostate cells and bothersome lower urinary tract symptoms. Current therapies for BPH provide both symptomatic relief and are disease modifying. However, they are associated with treatment limiting adverse effects. Accordingly, safer and effective alternatives to conventional treatments are required. Prostogrit is a novel, Ayurvedic medicine, indicated for the treatment of BPH. The objective of the current study was to evaluate the pharmacological effects of Prostogrit in rat model of BPH.MethodsUltra high performance liquid chromatography was employed to detect and quantify the phytocompounds present in Prostogrit. BPH was induced in male Sprague Dawley (SD) rats by subcutaneous administration of testosterone propionate (TP) + estradiol benzoate (EB). Rats were administered Prostogrit at the doses of 10, 30, 100 and 300 mg/kg, twice daily (b.i.d.). Finasteride administered once daily (q.d.) at the dose of 1 mg/kg was employed as the method control. The experimental readouts included measurements of the weights of prostate, seminal vesicles and urinary bladder; histological evaluation of prostatic tissue along with mRNA expression of alpha 1A adrenoceptor (Adra1a) and interleukin 6 (Il6) genes.ResultsPhytochemical analysis of Prostogrit revealed the presence of phytometabolites, namely guggulsterone, gallic acid, 5-hydroxymethylfurfural (5-HMF), methyl gallate, cinnamic acid and piperine. In the in vivo experiment, Prostogrit restored the TP+EB-induced increase in the relative weights of prostate and urinary bladder. It ameliorated the TP+EB-evoked epithelial proliferation, acinar hypertrophy and infiltration of inflammatory cells in the prostate stroma, in a dose-dependent fashion. Additionally, Prostogrit could also suppress the TP+EB-induced increase in the mRNA expression of Adra1a and Il6 genes in prostatic tissue.ConclusionThe findings of the current proof of concept study suggest that Prostogrit has pharmacological effects in an animal model of BPH. Accordingly, it possesses preclinical potential for the pharmacotherapeutic management of BPH, which merits further investigations.